Predicting Visuospatial and Verbal Working Memory by Individual Differences in E-Learning Activities - Fellman, Daniel; Lincke, Alisa; Berge, Elias; Jonsson, Bert (Frontiers in Education, 2020)
E-learning is being considered as a widely recognized option to traditional learning environments, allowing for highly tailor-made adaptive learning paths with the goal to maximize learning outcomes. One aspect crucial for learning success that is relatively unstudied in relation to e-learning is working memory (WM), conceptualized as the ability to maintain and manipulate incoming information before it decays. The aim of the present study was to examine how individual differences in online activities is related to visuospatial- and verbal WM performance. Our sample consisted of 90 participants studying on an e-learning platform. We extracted 18 relevant features of online activity features tapping on Quiz accuracy, Study frequency, Within-session reading activity, and Repetitive behaviour. Using best subset multiple regression analyses, the results showed that individual differences in online activities can be mapped more by verbal WM, but less so by visuospatial WM. The obtained results contribute to the existing research of WM in e-learning environments, and further suggest that individual differences in verbal WM tasks is an important factor to take into account when personalizing adaptive e-learning platforms to individual needs.